2018
DOI: 10.1590/2317-1782/20182017088
|View full text |Cite
|
Sign up to set email alerts
|

Deglutição orofaríngea, nutrição e qualidade de vida no indivíduo com doença pulmonar crônica

Abstract: Changes in efficacy and safety of deglutition were observed; however, no nutritional risk was evidenced in the sample evaluated. Correlation between nutritional risk and quality of life in deglutition was also observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
1
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 17 publications
0
1
0
4
Order By: Relevance
“…A prevalência da disfagia em pacientes com doenças pulmonares varia entre 52% a 78% 3,5,12,17 , pode levar à piora da função ventilatória com maior chance de internação hospitalar 3 , e aumento da morbidade e mortalidade devido ao alto risco de pneumonia aspirativa e desnutrição 17 . Assim sendo, torna-se fundamenta a adoção de cuidados para prevenção de complicações clínicas 3,12 , que podem ser minimizadas pelo rastreamento das alterações de deglutição e intervenção precoce.…”
Section: Discussionunclassified
See 3 more Smart Citations
“…A prevalência da disfagia em pacientes com doenças pulmonares varia entre 52% a 78% 3,5,12,17 , pode levar à piora da função ventilatória com maior chance de internação hospitalar 3 , e aumento da morbidade e mortalidade devido ao alto risco de pneumonia aspirativa e desnutrição 17 . Assim sendo, torna-se fundamenta a adoção de cuidados para prevenção de complicações clínicas 3,12 , que podem ser minimizadas pelo rastreamento das alterações de deglutição e intervenção precoce.…”
Section: Discussionunclassified
“…Logo, esses cuidados favorecem o resultado funcional adequado, melhor qualidade de vida e redução dos custos institucionais 10 . Doenças pulmonares podem levar à redução do volume pulmonar, comprometimento da capacidade do ar inspirado e expirado, menor tempo de apneia da deglutição, incoordenação entre deglutição e respiração e favorecer episódios de estase e de aspiração 2,3,4,6,17 , os quais podem piorar a condição clínica do paciente.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…A previous study suggested that the reduction of the orofacial muscular strength could compromise the swallowing efficiency and safety, which can be associated with the lack of coordination with the breathing process (22) . The literature also emphasizes a necessity of taking longer breathing breaks during feeding and a reduced apnea break while swallowing, which increases the risk of oropharyngeal dysphagia (25) . Despite observing swallowing alteration in 64.2% of the assessed subjects, not all of them received an indication of consistency restriction due to adequate functional compensation, guaranteeing a safe ingestion Dysphagia in older adults with fractures without restrictions.…”
Section: Discussionmentioning
confidence: 99%